1997
DOI: 10.1111/j.1465-7287.1997.tb00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Inspection and Maintenance Programs to Regulate Vehicle Emissions

Abstract: Policymakers have hoped that vehicle inspection and maintenance programs would generate air quality improvements at low cost. Existing programs have been unsuccessful because they have failed to provide consumers with incentives to maintain their vehicles so as to have low in-use emissions. This paper examines the reasons why existing inspection and maintenance programs have failed and investigates how they might be improved. Copyright 1997 Western Economic Association International.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 6 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…7 The fact that a small percentage of vehicles contributes a large share of the total stock of emissions suggests that effective inspection and maintenance programs could significantly reduce California smog. Unfortunately, private garages and motorists do not face the right incentives to diagnose and repair vehicles with extremely high emissions (Hubbard, 1997). A more cost-effective means of reducing such vehicles' emissions would be to use remote sensing to identify high polluters for required repair (see http://www.rppi.org/ smogcheck.html).…”
Section: Measuring Vehicle Emissions Progress By Model Yearmentioning
confidence: 99%
“…7 The fact that a small percentage of vehicles contributes a large share of the total stock of emissions suggests that effective inspection and maintenance programs could significantly reduce California smog. Unfortunately, private garages and motorists do not face the right incentives to diagnose and repair vehicles with extremely high emissions (Hubbard, 1997). A more cost-effective means of reducing such vehicles' emissions would be to use remote sensing to identify high polluters for required repair (see http://www.rppi.org/ smogcheck.html).…”
Section: Measuring Vehicle Emissions Progress By Model Yearmentioning
confidence: 99%
“…In Beijing, according to Kebin and Chang, (1999) (Faiz et al, 1996). Contrary to the aforementioned studies, Hubbard (1997) argued that the existing I/M programs in the United States have generated, at most, small environmental benefits.…”
Section: Vehicle Inspection and Maintenance Programsmentioning
confidence: 90%
“…Although it is believed that these traditional I/M programs have contributed to the improvement of air quality, their effectiveness has been criticized for years [3][4][5]. Some recent studies [4][5][6][7] showed that, the actual vehicle on-road emissions are usually much higher than those which are measured during the emission inspections. Although remote sensing has been introduced for non-scheduled on-road inspections, it still suffers potentially from the problems that the drivers may be able to avoid the inspection [6].…”
Section: Introductionmentioning
confidence: 95%
“…Some recent studies [4][5][6][7] showed that, the actual vehicle on-road emissions are usually much higher than those which are measured during the emission inspections. Although remote sensing has been introduced for non-scheduled on-road inspections, it still suffers potentially from the problems that the drivers may be able to avoid the inspection [6]. Therefore, it is desired to design a new vehicle emission inspection and control system that can truly reflect the vehicles' emission condition, as well as effectively notify the vehicle owners and the governmental authorities of the vehicles' health.…”
Section: Introductionmentioning
confidence: 96%